Spending Disparities Between High and Low Spenders in Gaming: Case Study “Call Me Emperor” - Pham, Phuong Minh (Digital Repository of Theses, 2025)
Mobile games have become a dominant force in the entertainment industry, prompting an investigation into the motivations behind in-game spending. Current research largely focuses on the social and psychological impacts of gaming, lacking practical insights into the commercial success of specific game models. This study aims to identify the factors driving player spending in mobile games, using "Call me Emperor" as a case study, and propose a commercially viable game model. A mixed-methods approach, including interviews with industry professionals and gamers, was employed to analyze player motivations and spending patterns. Results indicate that a combination of psychological, social, and neuroscience factors, particularly the use of compelling non-player characters (NPCs) and strategic monetization, significantly influences player spending. This research concludes that a formula exists to create commercially successful mobile games by understanding and leveraging these factors. Future research should explore the long-term effects of specific game mechanics on player retention and spending behavio